2022
DOI: 10.1002/jper.22-0027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the subgingival microbiome and menopausal hormone therapy use: The Buffalo OsteoPerio study

Abstract: Background This study investigated the association between menopausal hormone therapy (HT) use and the subgingival microbiome, for which published information is limited. Methods This cross‐sectional study included 1270 postmenopausal women, aged 53–81 years, who completed clinical examinations. Detailed information on HT use (type, delivery mode, duration) was obtained from questionnaires. HT use was categorized into three groups (never, former, current). 16S rRNA sequencing was performed on subgingival plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…( 47 ) reported that the abundance of Synergistetes was significantly higher in the postmenopausal osteopenia group than in the control group, and Soliman et al. ( 48 ) showed that bacterial OUTs (operational taxonomic units) belonging to the phylum Synergistetes were higher in women who did not receive hormone replacement therapy during menopause. However, the differences in relative taxa levels between pre- and postmenopausal controls or BC patients were weak in our study.…”
Section: Discussionmentioning
confidence: 99%
“…( 47 ) reported that the abundance of Synergistetes was significantly higher in the postmenopausal osteopenia group than in the control group, and Soliman et al. ( 48 ) showed that bacterial OUTs (operational taxonomic units) belonging to the phylum Synergistetes were higher in women who did not receive hormone replacement therapy during menopause. However, the differences in relative taxa levels between pre- and postmenopausal controls or BC patients were weak in our study.…”
Section: Discussionmentioning
confidence: 99%